Preclinical screening for cardiovascular disease with high-sensitivity cardiac troponins: ready, set, go? - Awwad, Aya; Parashar, Yashika; Bagchi, Soahum; Siddiqui, Saman Asad; Ajari, Ogheneochuko; deFilippi, Christopher (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular disease (CVD), including atherosclerosis, valvular etiologies, or myocardial disorders is typically asymptomatic for years, representing an occult phase of illness. Readily available preventive treatments to reduce cholesterol and blood pressure among other risk factors have the potential to reduce and delay incident myocardial infarction (MI), heart failure (HF) and cardiovascular (CV) deaths.Measurement of circulating levels of cardiac troponin T (cTnT) and troponin I (cTnI) released from cardiomyocytes, as the result of injury, have been the biochemical standard for the diagnosis of MI for more than 20 years. The recent adoption of high-sensitivity (hs) assays, which are capable of measuring cTnT and I levels in more than 50% of the general population, has revealed a clear association between progressively higher biomarker levels and future CV events. cTn levels measured by hs assays have also demonstrated correlations between elevated biomarker levels and occult CVD such as coronary artery disease and myocardial fibrosis in cross-sectional imaging studies. In this review, we provide evidence to consider measuring hs-cTnT and hs-cTnI to screen for patient CV risk and provide an example of a scenario in which such screening may improve outcomes through decision support for aggressive management of blood pressure.